Integrasi Green–Blue Infrastructure untuk Ketahanan Iklim dan Air di Nusa Tenggara Timur: Sebuah Systematic Literature Review dari Perspektif Semi-Arid Urban Systems - Bara, Alvin Alfredo; Cornelis, Remigildus; Lau, Debora (Jurnal Kridatama Sains dan Teknologi, 2025)
The semi-arid region of East Nusa Tenggara (NTT) faces increasing environmental pressures, including prolonged droughts, rising surface temperatures, and rapid runoff during short, intense rainfall events. These conditions necessitate nature-based solutions to restore hydrological balance and strengthen climate resilience. This study aims to identify the effectiveness of Green Infrastructure (GI) and Blue Infrastructure (BI) in addressing water scarcity and urban heat challenges, and to formulate an integrated GI–BI model that is adaptive to the socio-ecological conditions of NTT. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines by examining nine recent international publications on GI–BI performance in semi-arid regions. Synthesis of the nine studies indicates that combinations of GI elements (bio-retention, green roofs, vegetated spaces, street trees) and BI components (retention ponds, natural channels, micro-reservoirs) consistently contribute to restoring 82–90% of pre-development water balance, reducing runoff by 35–45%, and lowering air temperatures by 3–5°C, depending on spatial configuration and local climatic variability. Key barriers to implementation include limited financing, weak cross-sectoral coordination, and insufficient long-term performance data. These findings underscore that GI–BI functions not only as technical interventions but also as critical policy instruments for adaptive spatial planning, green financing frameworks, and remote-sensing–based environmental monitoring in NTT. The study highlights the urgency of developing an integrated long-term implementation framework to ensure the sustainability of GI–BI adoption in enhancing regional climate resilience